Acute Quadriparesis in Dengue - A Rare Presentation of a Common Disease - Swapan Nagpal; Amar Jeet Singh Nagpal (Indian Journal of Medical Specialities)
Dengue fever commonly presents with electrolyte abnormalities including hypokalemia. Hypokalemic quadriparesis is a very rare manifestation of this common arboviral infection. We report a case of acute reversible quadriparesis caused by hypokalemia in a patient with dengue. Such a presentation has been reported very few times. Various mechanisms have been proposed to explain hypokalemia in dengue, and it is still not completely known why some patients develop motor weakness and others do not. Most such cases have a very good prognosis and the weakness resolves on potassium supplementation.